Planejamento estrutural visando otimização da atividade tripanocida de análogos sintéticos da piplartina - Bezerra Filho, Carlos da Silva Maia (2020)
Chagas disease is considered one of the main neglected tropical diseases and represents a major public health problem due to the high rates of associated morbidity and mortality. Currently, the drugs available for the treatment of the disease are outdated, have limited efficacy and severe adverse and/or side effects that result in nonadherence to treatment and reduced quality of life for patients. Therefore, it is necessary to search for new therapeutic alternatives that promote greater selectivity to the parasite that causes the disease, as well as drugs with new mechanisms of action and that have good efficacy. Piplartine, also known as piperlongumin is a phenylpropanoid, found in plants of the genus Piper, data from the literature report that piplartine has several biological activities, including trypanocidal activity. Thus, the objective of the present work was to prepare a collection of thirteen piplartine analogs esters (01 - 13), structurally related, and evaluate the trypanocidal activity of the compounds against Trypanosoma cruzi, as well as to establish the structureactivity relationship of assessed substances. The esters were prepared using three different methodologies: Fischer esterification, esterifications with alkyl and aryl halides and Steglich reaction. In the structural characterization, the spectroscopic techniques of Infrared, Nuclear Magnetic Resonance of 1H and 13C were used. The products were obtained with yields of 26.7–91.1%. The trypanocidal tests were performed against the evolutionary forms epimastigote and trypomastigote using the microdilution technique in 96-well plates to determine the concentration capable of inhibiting the growth of the parasite by 50% (IC50), in addition, the cytotoxicity of the compounds against Rhesus monkey renal epithelial cells (LLC-MK2) for the calculation of the selectivity index (SI). The compound 10 showed good trypanocidal activity against the trypomastigote form (IC50 = 40.75 ± 12.36 μM). While 11 was bioactive in both evolutionary forms with IC50 = 28.21±5.34 μM and 47.02±8.70 μM (epimastigote and trypomastigote, respectively), besides to presenting a high selectivity index to the parasite (SI > 10). In the investigation of the trypanocidal mechanism of action, it was elucidated that it occurs through the induction of oxidative stress and mitochondrial damage to the parasite cells. Therefore, the present study demonstrates the antiparasitic potential of this chemical class for the search for new drugs with trypanocidal activity.